2017
DOI: 10.1080/09687637.2017.1353063
|View full text |Cite
|
Sign up to set email alerts
|

Challenging, co-operating and splitting: a qualitative analysis of how the trade press responded to cumulative impact policies in England and Wales

Abstract: At the time of writing, Dorothy Hector was a Masters student at the London School of Economics and Political Science. She is currently attending Harvard Law School and her interests include health law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Concerning the SDIL, a media analysis starting a year before the announcement of the policy suggested that articles supportive of SSB taxation (23.5%) outnumbered those that were oppositional (14.2%) [ 28 ] and that arguments underpinning proponents and opponents of the SDIL were broadly consistent with those used within the alcohol and tobacco industry [ 29 ]. While most of the research examining media representations of industry and their discursive strategies is focused on message framing [ 30 ], there is evidence that industry messaging can shift depending on the audience, with conflicting or contradictory debates and responses to regulation [ 31 , 32 ]. Therefore, examining industry reactions throughout policy development and implementation processes could offer novel insights into how industry messaging evolves in a changing political landscape over time.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the SDIL, a media analysis starting a year before the announcement of the policy suggested that articles supportive of SSB taxation (23.5%) outnumbered those that were oppositional (14.2%) [ 28 ] and that arguments underpinning proponents and opponents of the SDIL were broadly consistent with those used within the alcohol and tobacco industry [ 29 ]. While most of the research examining media representations of industry and their discursive strategies is focused on message framing [ 30 ], there is evidence that industry messaging can shift depending on the audience, with conflicting or contradictory debates and responses to regulation [ 31 , 32 ]. Therefore, examining industry reactions throughout policy development and implementation processes could offer novel insights into how industry messaging evolves in a changing political landscape over time.…”
Section: Introductionmentioning
confidence: 99%
“…It is timely to consider whether economic prosperity in the NTE must rely on alcohol and whether there is a third way or ‘sweet spot’ approach via policies which transform and build the NTE to prioritise other forms of entertainment, food, music or more family‐friendly environments. The nature of such policies and their feasibility and acceptability to communities [ 48 , 49 ] and trade stakeholders [ 50 ], plus their likely and actual effectiveness in balancing prosperity and reducing harms, requires further consideration and research. Strategic planning policies at local authority level [ 51 ], availability and promotion of no/very low alcohol products [ 52 ] and ‘place‐shaping’ in the licensing system, through which premises perceived as lower risk (restaurants, arts venues) are prioritised in licensing policy over others with a strong alcohol focus [ 48 ] may all have a role to play.…”
Section: Discussionmentioning
confidence: 99%
“…It is timely to consider whether economic prosperity in the NTE must rely on alcohol and whether there is a third way or 'sweet spot' approach via policies which transform and build the NTE to prioritise other forms of entertainment, food, music or more family-friendly environments. The nature of such policies and their feasibility and acceptability to communities [48,49] and trade stakeholders [50], plus their likely and actual effectiveness in balancing prosperity and reducing harms, requires further consideration and research.…”
Section: Reductions In Alcohol Burden On Ambulance Services During Lo...mentioning
confidence: 99%